2020
DOI: 10.1093/narcan/zcaa032
|View full text |Cite
|
Sign up to set email alerts
|

The chemotherapeutic agent CX-5461 irreversibly blocks RNA polymerase I initiation and promoter release to cause nucleolar disruption, DNA damage and cell inviability

Abstract: In the search for drugs to effectively treat cancer, the last 10 years have seen a resurgence of interest in targeting ribosome biogenesis. CX-5461 is a potential inhibitor of ribosomal RNA synthesis that is now showing promise in phase I trials as a chemotherapeutic agent for a range of malignancies. Here, we show that CX-5461 irreversibly inhibits ribosomal RNA transcription by arresting RNA polymerase I (RPI/Pol1/PolR1) in a transcription initiation complex. CX-5461 does not achieve this by preventing forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 76 publications
7
52
0
Order By: Relevance
“…At later times, Ubtf became highly condensed and partially segregated from RPI while FBL dispersed throughout the nucleus (120 h and 144 h post 4-HT in Figures 1D and S3). These changes were consistent with the nucleolar changes previously observed on inactivation of RPI transcription either by Rrn3 gene deletion or CX-5461 drug inhibition (24,28).…”
Section: Taf1b Deletion Induces Nucleolar Stresssupporting
confidence: 91%
See 1 more Smart Citation
“…At later times, Ubtf became highly condensed and partially segregated from RPI while FBL dispersed throughout the nucleus (120 h and 144 h post 4-HT in Figures 1D and S3). These changes were consistent with the nucleolar changes previously observed on inactivation of RPI transcription either by Rrn3 gene deletion or CX-5461 drug inhibition (24,28).…”
Section: Taf1b Deletion Induces Nucleolar Stresssupporting
confidence: 91%
“…Hence, as observed for the other RPI basal factors Ubtf and Rrn3, Taf1b is an essential factor in mouse. Conditional deletion of taf1b in MEF and mES cell culture was also found to arrest rDNA transcription and to cause severe disruption of nucleolar structure characteristic of nucleolar stress (24,28). Depletion of Taf1b also prevented promoter recruitment of Taf1c and TBP subunits of SL1 and hence PIC formation at both the 47S pre-rRNA and the Enhancer-associated Spacer rDNA promoters.…”
Section: Discussionmentioning
confidence: 89%
“…Here, it was found that the mechanism of cell death is through Topoisomerase II poisoning [ 129 ]. Mars et al also found that CX-5461 blocks the release of RNAPI-RRN3 and blocks transcription initiation [ 130 ]. Perhaps CX-5461 has multiple mechanisms of action that could depend on cell context—an interesting avenue to explore.…”
Section: Therapeutic Targeting Of Rrna Synthesis To Treat Breast Cancermentioning
confidence: 99%
“…At the exit from mitosis, pre-rRNA synthesis resumes and the nucleolus reassembles its tripartite structure, when CDK1 activity is suppressed and RNAPI transcription is reactivated [ 36 , 37 , 38 ]. Along the same lines, the nucleolus disintegrates upon specific induction of nucleolar DNA damage or selective impairment of RNAPI transcription [ 39 , 40 , 41 , 42 ]. The inhibition of early steps in pre-rRNA processing also leads to nucleolar stress, along with the nucleoplasmic translocation of nucleolar proteins and the formation of ‘nucleolar caps’ [ 16 , 43 ].…”
Section: The Nucleolus Is a Multifunctional Rna Metabolic Hubmentioning
confidence: 99%